'It's still them': concealed racism against Roma in Romanian television news. (2nd January 2022) - Breazu, Petre; Machin, David
ABSTRACT: Research shows that news media around the world carry negative representations of ethnic minorities which incite violence, hatred or lead to more marginalisation and social exclusion [Bhatia, M., Poynting, S., & Tufail, W. (2018). Media, crime and racism . Springer; Elias, A., Mansouri, F., & Paradies, Y. (2021). Media, public discourse and racism. In A. Elias, F. Mansouri, & Y. Paradies (Eds.), Racism in Australia today (pp. 211–240). Palgrave Macmillan]. It is also the case that overt racism has become less tolerated in society and, therefore, racist discourses now tend to take more subtle forms, often disguised as reasonable concerns about threats to national culture, economic burdens or disruptions of social order [Bonilla-Silva, E. (2006). Racism without racists: Color-blind racism and the persistence of racial inequality in the United States . Rowman & Littlefield]. This is very much the case regarding the Roma. Yet, less research has been carried out on the way that the affordances of television – juxtaposition of images, captions, sound and voice-overs, editing, and resequencing – may have very specific ways to conceal racism. In this paper, using Multimodal Critical Discourse Analysis, we examine the representation of the Roma in a Romanian television news report, in the case of a highly mundane story – a failure to pay electricity bills. We show how television news with its affordances can camouflage racism, and distract from the extreme poverty and social exclusion that Romani people experience in contemporary Europe.